Analysis of The Influence of Reading Speed and Reading Reference on Reading Comprehension Skills With Reading Strategy as Mediation Variables for Students at State University of Padang - Amril Amir (JETL (Journal of Education, Teaching and Learning), 2023)
This study aims to analyze the analysis of the effect of reading speed and reading frequency on reading comprehension skills with reading strategy as a mediating variable for students of Universitas Negeri Padang. This research is a quantitative method with a descriptive type. The sampling technique in this study used the nonprobability sampling method, namely the purposive sampling technique. Data was collected using a questionnaire in the form of a Likert scale with five alternative answers. The data analysis technique used SEM-PLS with SmartPLS version 3 software. The results of the study found that reading speed had a direct and significant effect on reading comprehension skills. Reading frequency has a direct and significant effect on reading comprehension skills. Reading strategy have a direct and significant effect on reading comprehension skills. Reading speed has a direct and significant effect on reading strategy. Reading frequency has a direct and significant effect on reading strategy. There is an effect of reading speed on reading comprehension skills mediated by reading strategy. There is an effect of reading speed on reading comprehension skills mediated by reading strategy.